American empire and the politics of meaning elite political cultures in the Philippines and Puerto Rico during U.S. colonialism - Go, Julian 1970- (Politics, history, and culture, 2008)
Introduction: Colonialism and Culture in the American Empire -- Chapter 1: Tutelary Colonialism and Cultural Power -- Chapter 2: Domesticating Tutelage in Puerto Rico -- Chapter 3: Winning Hearts and Minds in the Philippines -- Chapter 4: Beyond Cultural Reproduction -- Chapter 5: Divergent Paths -- Chapter 6: Structural Transformation in Puerto Rico -- Chapter 7: Cultural Revaluation in the Philippines -- Conclusion: Returning to Culture